IMPLEMENTASI TEORI BELAJAR HUMANISTIK DALAM PEMBELAJARAN AQIDAH AKHLAK KELAS V MI ISLAMIYAH WONOKITRI KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Nurul Junida; Sri Enggar Kencana Dewi; Ratih Purnama Pertiwi (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to describe the implementation of humanistic learning theory in learning aqeedah morals of class V MI Islamiyah Wonokitri. This type of research is descriptive qualitative using observation, interviews, and documentation as data collection procedures. Checking the validity of the findings is done by source triangulation. The research subjects were the head of the madrasa, the teacher of aqidah morals and the fifth grade students of Mi Islamiyah Wonokitri. The research stages include the pre-field stage, the field worker stage, and the data analysis stage. The results of the study show that the implementation of humanistic learning theory in learning the moral principles of class V Mi Islamiyah Wonokitri, namely: at the planning stage a) the teacher determines the learning material to be delivered to students. b) the teacher determines the learning objectives to be achieved in learning. c) identify students' abilities related to the material to be provided. d) provide facilities in the form of learning resources and learning tools such as environment and books. e) guiding students to be able to understand the subject matter being taught. f) students evaluate at the end of learning to determine the ability of students' development in mastering learning material. at the implementation stage a) the activity begins with praying dhuha in congregation which is carried out every morning. b) the learning method used basically aims to make learning more interesting and fun. c) the teacher acts as a facilitator and motivator. d) factors that support learning, namely the environment and learning resources. e) the factor that hinders the humanistic learning process is the lack of learning facilities and infrastructure. at the stage of evaluating the implementation of humanistic learning theory. Evaluation is carried out by taking into account three aspects, namely, knowledge, attitudes and skills. Evaluation is carried out at the end of learning and also during midterm exams and year-end exams.